Discursive Construction of Identity in Postcolonial Literature: The Case of Chimamanda Ngozi Adichie’s Americanah - Kara, Nadjah; Meftah, Safa (University of Eloued جامعة الوادي, 2024)
This research examines the rhetorical techniques employed in the novel Americanah to explore how identity was shaped in the postcolonial period. It highlights the relationship between race, gender, and nationality in creating and developing a postcolonial identity, examining how the characters interact with each other across various geographical, cultural, and social circumstances. The discourse analytical method is adopted to explore the rhetorical construction of identity and to provide a representation of the characters' experiences of migration, cultural hybridity, and the legacy of colonialism, which shape the discursive construction of postcolonial identity. Adichie uses code-switching, dialect, and metaphor to convey the complexities of postcolonial identity. The main result of this dissertation revealing postcolonial identity through narration and language in Americanah is that Ifemelu represents Afropolitanism, navigating cultural dynamics in Nigeria and the US. She reflects on race, immigration, and belonging in a globalised society on her blog, which shapes her evolving identity. It investigates language use, power relatiيتناول هذا البحث التقنيات البلاغية التي تم توظيفها في رواية أمريكانا التي كتبتها تشيماماندا نغوزي أديتشي لاستكشاف كيفية تشكيل الهوية في فترة ما بعد الاستعمار. يسلط الضوء على العلاقة بين العرق والجنس والجنسية لخلق وتطوير هوية ما بعد الاستعمار، كما يدرس الطريقة التي تتفاعل بها الشخصيات مع بعضها البعض داخل الرواية عبر مختلف الظروف الجغرافية والثقافية والاجتماعية. تقدم هذه الدراسة تمثيلاً للمؤلف الذي يعكس تجارب الشخصيات في الهجرة والتهجين الثقافي وإرث الاستعمار، وتشكل البناء الخطابي للهوية ما بعد الاستعمارية في أمريكانا. تستخدم أديتشي تبديل الرموز واللهجة والاستعارة لنقل تعقيدات هوية ما بعد الاستعمار، ويعكس التفاوت على هويات ما بعد الاستعمار في أمريكانا قضايا العنصرية والعولمة والشتات. ومن هذا المنطلق، تم اعتماد منهج تحليل الخطاب في هذا البحث لاستكشاف البناء الخطابي للهوية في أدب ما بعد الاستعمار، مع التركيز على رواية أمريكان كمجموعة أدبية. والنتيجة الرئيسية لهذه الأطروحة هي الكشف عن هوية ما بعد الاستعمار من خلال السرد واللغة في رواية "أمريكانا". تتأمل في العرق والهجرة والانتماء في مجتمع معولم على مدونتها التي أدت إلى تشكيل هويتها المتطورة.ons, and social contexts.
الهوية، أدب ما بعد الاستعمار، أمريكانا، البناء الخطابي
Keywords: Identity; Postcolonial literature; Americanah; Discursive Construction; Discourse; الهوية، أدب ما بعد الاستعمار، أمريكانا، البناء الخطابي